LITERATURE REVIEW: PENGGUNAAN OBAT ANTIBIOTIK PADA PASIEN PNEUMONIA - Yuliana, Dewi; A, Miftahul Janna (PHARMACY UMI JOURNAL SYSTEM, 2024)
Pneumonia is an acute inflammatory disease of the lung parenchyma which usually results from an acute lower respiratory tract infection with coughing and shortness of breath. The purpose of this study was to find out how to use antibiotics in pneumonia patients. The research method is that this study uses literature reviews, in searching literature sourced from 2 databases (Pubmed and Google Scholar) using keywords according to the theme. Unlike previous studies, this study focuses on the use of antibiotic drugs in pneumonia patients. The amount of literature used is 13 journal articles